2011
DOI: 10.1016/j.seizure.2010.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraperitoneal administration of the phenytoin on the skeletal system of rat fetus

Abstract: This study was conducted on determining the effects of phenytoin on the skeletal system of the fetuses of 13 Wistar Albino rats. The female rats were divided into two groups after the vaginal smear test: the group 1 (control group) included 6 individuals, whereas the group 2 (phenytoin group) comprised 7 animals. A dose of 25mg/kg/day phenytoin was administered intraperitoneally to pregnant rats on the 8th-10th days of pregnancy and fetuses were obtained by C-section on the 20th day. A number of 82 fetuses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…Harbison and Becker [53] and Mansoor et al [56] have reported a worsening in the ossification process of the long bones in the mouse and rat fetuses of the PHT treated mothers, but such a finding was not observed in the present work. Soysal [13] and Mansoor et al [56] reported costal anomalies in the form of costal separation, while Kim et al [55] have reported costal anomalies in the form of absent, short and discontinuous ribs, and absent ossification of some sternebrae in the fetuses of PHT treated rats. However, our study showed absence of ossification centre of one sternebra and costal separation in the pups of the PHT-treated mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harbison and Becker [53] and Mansoor et al [56] have reported a worsening in the ossification process of the long bones in the mouse and rat fetuses of the PHT treated mothers, but such a finding was not observed in the present work. Soysal [13] and Mansoor et al [56] reported costal anomalies in the form of costal separation, while Kim et al [55] have reported costal anomalies in the form of absent, short and discontinuous ribs, and absent ossification of some sternebrae in the fetuses of PHT treated rats. However, our study showed absence of ossification centre of one sternebra and costal separation in the pups of the PHT-treated mothers.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] PHT has been documented to be a teratogenic agent in both mice and rats. [13] It is believed that PHT produces anomalies in 34% of fetuses which are exposed to it. [14] Cleft lip (CL) is a common malformation that has both genetic and exogenous causes.…”
Section: Introductionmentioning
confidence: 99%
“…Soysal et al (17) using 25mg/kg/day phenytoin administered intraperitoneally to pregnant rats detected that fetuses were 14% shorter and the weights 13% lower compared to control animals with decreased number of the fetuses obtained in one gestation by 9%, and deteriorated ossification of skull bones, costal separation anomaly, the laterally-separated costal components were not attached to the costal arch with shape malformations in the last two ribs and wide angularity, particularly in the last six ribs.…”
Section: Discussionmentioning
confidence: 99%
“…Mice and rats exposed to valproic acid exhibited abnormal limbs including long bone reductions and abnormal or missing digits [25,27,28,38]. Similarly, rat fetuses maternally subjected to intraperitoneal injection of phenytoin suffered from deteriorated ossification of skull bones and costal separation anomaly [2,39].…”
Section: Gbp + Ginger Groupmentioning
confidence: 99%
“…Due to relapsing and severity of epilepsy, many women cannot stop using medications even during pregnancy [1]. It is a well-documented fact that teratogens affect the development of embryo, mostly during the process of organogenesis, which starts on GD 6 in rats and continues to GD 15 [2]. Currently, management of epilepsy mainly depends on antiepileptic drugs (AEDs), which are notoriously known for their adverse side effects and this explains the reason for their several generations.…”
Section: Introductionmentioning
confidence: 99%